Potensi Pemanfaatan Gas Karbon Dioksida (CO2) sebagai Density Agent untuk Larutan Pemisah Cangkang dan Kernel Sawit - Muhammad Muhammad; Marwan Marwan; Muhammad Zaki; Edi Munawar (Fakultas Teknik, 2022)
In order to achieve the national target of decarbonization by 2030, Palm oil mills (POM) can contribute to reducing CO2 emissions generated from their production activities. The CO2 emitted from POM is currently discharged into the environment without further treatment. As a result, the amount of CO2 in the atmosphere will rise, increasing global warming. This study proposes an approach of utilizing CO2 as a density agent in separation fluid formulation. The formulated fluid is then used to separate palm shells and kernels in the claybath. The solubility of CO2 in water occurs physically and is dependent on temperature and partial CO2 gas in the air. Monoethanolamine (MEA) was used as an absorbent to ensure the full interaction of CO2 with water. The chemisorption method is selected to dissolution CO2 into aqueous MEA. The mass ratios of MEA were varied by 10, 20, 30, 40, 50 % w/w. The achieved appropriate densities of formulated fluid were 1,11, 1,14, dan 1,17 g/cm3 at mass ratios of MEA:H2O is 30, 40, dan 50% w/w, respectively. All achieved densities fall between palm shells and kernels densities. Furthermore, the formulated fluid can be used as separation fluid in claybath for separating palm shells and kernels. In addition to the proposed idea of utilizing CO2 and, at the same time, reducing CO2 emission from POM.